A study to assess the knowledge, attitude and practice regarding handwashing during covid-19 pandemic among ASHA workers working under RHTC Najafgarh, Delhi, NCR - Bargoti, Abha; Pal, Monalisha (International Journal Of Community Medicine And Public Health, 2023)
Background: The World Health Organization (WHO) has declared the coronavirus disease 2019 (COVID-19) a pandemic. Hand hygiene is a highly cost-effective investment, providing outsized health benefits for relatively little cost; truly a ‘no-regrets’ investment. In this study researcher want to assess the knowledge, practice and attitude of ASHA workers regarding hand washing during COVID-19 pandemic. Methods: In this study interpretation of data collected from 100 ASHA workers through a structured knowledge questionnaire to assess the knowledge and Likert scale to assess the attitude and practice regarding hand washing during Covid-19 pandemic among ASHA workers. The non- probability, convenient sampling technique was used to select samples. Results: The results showed that (66%) of ASHA workers had average knowledge, the remaining (31%) had good knowledge, (3%) had poor knowledge. Conclusions: The study reveals the level of knowledge, attitude and practice of ASHA worker regarding hand washing during covid 19 pandemic was average. It suggests a need for improvement of hand hygiene practices and knowledge among health professional working under covid 19 pandemic.